2009
DOI: 10.1007/s00228-009-0767-8
|View full text |Cite
|
Sign up to set email alerts
|

Atazanavir plasma concentrations are impaired in HIV-1-infected adults simultaneously taking a methadone oral solution in a once-daily observed therapy setting

Abstract: Objective The human immundeficiency virus (HIV) protease inhibitor atazanavir is often used in once-daily observed therapy of methadone substituted former opiate drug users. We performed a matched-pairs analysis on 24 patients (12 men/women) taking atazanavir/ritonavir 300/100 mg daily plus reverse transcriptase inhibitors, with (n=12) or without (n=12) methadone co-administration. Methods Twenty-four-hour pharmacokinetic profiles of atazanavir/ritonavir were assessed at steady-state and measured by liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…ATV and RTV pharmacokinetic parameters obtained in this study in the presence of CEP-1347 were comparable to values that have been previously reported. The estimated mean clearance of atazanavir (12.0 and 9.3 L/h for visits 1 and 2) in the present study was higher than that previously reported in patients (8.5 L/h) (Haberl et al 2010), although a population analysis reported 12.9 L/h in patients given ATV/r at 300/100 mg/day, similar to our present study (Colombo et al 2006). For mean AUC0-24 and C max , estimates ranging from 40.2 to 49.6 h μg/mL and 4.0 to 4.5 μg/mL, respectively, were consistent with literature (Wang et al 2011).…”
Section: Discussionsupporting
confidence: 82%
“…ATV and RTV pharmacokinetic parameters obtained in this study in the presence of CEP-1347 were comparable to values that have been previously reported. The estimated mean clearance of atazanavir (12.0 and 9.3 L/h for visits 1 and 2) in the present study was higher than that previously reported in patients (8.5 L/h) (Haberl et al 2010), although a population analysis reported 12.9 L/h in patients given ATV/r at 300/100 mg/day, similar to our present study (Colombo et al 2006). For mean AUC0-24 and C max , estimates ranging from 40.2 to 49.6 h μg/mL and 4.0 to 4.5 μg/mL, respectively, were consistent with literature (Wang et al 2011).…”
Section: Discussionsupporting
confidence: 82%
“…There are 2 plausible explanations: intravenous drug use history and/ or methadone use are surrogate markers for hepatitis C seropositivity in this cohort or methadone co-administration affects plasma concentrations of ATV. The latter is supported by a pharmacokinetic study of the co-administration of methadone and ATV that demonstrated significantly lower maximum concentrations (Cmax) of plasma ATV in those on concomitant methadone [10]. However, in this previous study, despite lower ATV levels, there was no difference in the therapeutic efficacy of ATV.…”
Section: Discussionmentioning
confidence: 78%
“…When administered unboosted, atazanavir has no effect on CYP 2B6 and as expected no significant effect on methadone concentrations 223 . Of interest, 1 study did note decreased concentrations of atazanavir when co-administered with methadone compared to patients not receiving methadone, though the effect was only statistically significant for Cmax, and an increase in virologic failure was not observed 224 . The authors proposed that this result may be specific to the oral solution of methadone formulated in Germany, which is particularly viscous and may more readily complex with atazanavir to impair its absorption.…”
Section: Treatments For Opioid Use Disordermentioning
confidence: 76%
“…223 Of interest, 1 study did note decreased concentrations of atazanavir when co-administered with methadone compared to patients not receiving methadone, though the effect was only statistically significant for Cmax, and an increase in virologic failure was not observed. 224 The authors proposed that this result may be specific to the oral solution of methadone formulated in Germany, which is particularly viscous and may more readily complex with atazanavir to impair its absorption. In another real-world survey and pharmacokinetic study of patients with HIV receiving atazanavir-or lopinavirbased regimens, the patients who were also receiving methadone had lower troughs of atazanavir and lopinavir than their counterparts.…”
Section: Methadonementioning
confidence: 99%